QUALITY BY DESIGN APPROACH FOR ENHANCEMENT THE DISSOLUTION RATE OF LAFUTIDINE LIQUISOLID TABLETS (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The aim of present work was to enhancing the solubility and dissolution rate of the aquaphobic drug Lafutidine by liquisolid technique. Lafutidine is a H2-receptor antagonist BCS class II drug. Lafutidine compatibility with excipients was evaluated by FT-IR and DSC spectrum. Preliminary trial taken to check the effect of carrier to coating material ratio (R) and non-volatile solvent (PEG- 600) on pre compression and post compression characteristic. Flowable liquid retention potential (Ø -value) and Liquid load factors (Lf) were calculated for required amount of excipients necessary to preparing Lafutidine liquisolid tablet. A 32 full factorial design was employed to check the effect of carrier to coating material ratio R (X1) and PEG- 600 (X2) on hardness (Y1), angle of repose (Y2), % of Cumulative drug release at 5 min Q5 (Y3), and disintegration time (Y4). Multiple linear regression analysis, ANOVA and graphical representation of the influence of factor by 3D plots were performing by using Design expert 7.0. In this study, the following constraints were arbitrarily used for the selection of an optimized batch: Hardness: 3 to 5.5, Angle of repose: 25 to 30, % of Cumulative Drug Release at 5 min (Q5) > 27.09 % and Disintegration time <1.3 min. The desirability value of various dependent variables calculated for determining the optimized batch of tablet and it was also found to be nearer to one. Performance of optimized batch had no shown any significant change at the end of stability study.